Assessment of Alterations in the Expression of P53 and Cyclin-D Genes in COVID-19 Patients Before and After Remdesivir Treatment - Somayeh Arabzadeh; Sohameh Mohebbi; Zahra Faal; Neda Jalali; Kayvan Saeedfar (Journal of Genetic Resources)
Coronavirus disease-19 (COVID-19), caused by the new coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a worldwide pandemic. The disease primarily spreads through respiratory droplets and manifests with a wide range of symptoms, from mild respiratory illness to severe pneumonia, acute respiratory distress syndrome (ARDS), and multi-organ failure. The virus manipulates the host cell cycle to create a favorable environment for its replication and propagation. One of the key regulators of the cell cycle is cyclin-D, a protein essential for the G1 to S phase transition in the cell cycle, and P53, a critical tumor suppressor and regulator of cell cycle arrest and apoptosis. Therapeutic strategies, including antiviral drugs like Remdesivir, have shown varying efficacy in managing symptoms and reducing mortality. This study obtained blood samples from 30 COVID-19 patients before and after Remdesivir treatment and 20 healthy individuals. RNA was isolated, and cDNA was subsequently synthesized. The expression levels of the p53 and cyclin-D genes were then assessed using Real-time PCR. The results demonstrate that cyclin-D expression increased 9 times in COVID-19 patients compared to the control group (P<0.001), which remained unaffected by Remdesivir treatment. Conversely, p53 gene expression was reduced by 50% in the patient group compared to the control group (P<0.05). Treatment with Remdesivir increased P53 gene expression twofold compared to the control group (P<0.001). Furthermore, P53 gene expression positively correlated with CRP (C Reactive Protein) levels in both the control and patient groups (P<0.01). The study's findings indicate that certain symptoms of COVID-19 may be linked to the virus's impact on crucial cell cycle genes, such as cyclin-D and p53. Remdesivir, by reducing inflammation and inhibiting viral replication, can help restore normal expression levels of these genes. This may support the therapeutic benefits of using Remdesivir in treating COVID-19.